A method for preparing all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber

By using rotary tube technology to prepare low-defect sulfur-based glass composite sleeves in the preparation process of all-solid large-mode field sulfur-based glass PCF, the problem of high PCF transmission loss in the prior art is solved, and lower transmission loss and higher laser power transmission capability are achieved.

CN115849700BActive Publication Date: 2025-03-18SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211505443.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-03-18
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

The existing all-solid state large-mode field sulfur-based glass PCF has a high transmission loss and is difficult to transmit higher laser power.

Method used

Rotary tube technology is used to prepare low-defect sulfur-based glass composite casings. By forming a base sulfur-based glass composite casing and filling a sulfur-based glass rod, defects on the core/clad interface are significantly reduced, thereby reducing the transmission loss of the optical fiber.

Benefits of technology

It significantly reduces the transmission loss of all-solid-state large-mode field sulfur-based glass PCF to reach less than 1dB/m, meets some practical application needs, and improves the laser power transmission capability of optical fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115849700B_ABST
    Figure CN115849700B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing an all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber, comprising preparing a base chalcogenide glass composite sleeve, preparing a filling chalcogenide glass rod, preparing a base chalcogenide glass binding sleeve, preparing a chalcogenide glass composite thin rod, preparing a base chalcogenide glass thin rod, assembling a photonic crystal optical fiber preform, and drawing a photonic crystal optical fiber. The method for preparing an all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber of the present invention can significantly reduce defects on the core / cladding interface and reduce the transmission loss of the optical fiber. The present invention can prepare a flexible all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber with a maximum core diameter of 120 μm, and the minimum transmission loss of the optical fiber is <1 dB / m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass optical fiber preparation, and particularly relates to a preparation method of an all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber. Background Art

[0002] Chalcogenide glass is an amorphous material formed based on chalcogen elements (S, Se, Te). Chalcogenide glass optical fiber has a wide infrared spectral range and a high nonlinear coefficient, and has great application prospects in infrared laser transmission, thermal imaging transmission, nonlinear optics and other fields. Among them, most infrared laser transmission and nonlinear optical applications require that the optical fiber can transmit higher laser power in single mode. Because the chemical bonds that form the chalcogenide glass network structure are weak, its laser damage threshold is low. According to literature reports, the highest mid-infrared laser power that can be transmitted by single-mode chalcogenide glass optical fiber is only ~10W, and the optical fiber used is As-S step-index optical fiber with a core diameter of 12μm.

[0003] Since optical fiber materials are damaged above a certain laser power density, a direct and effective solution to increase the laser power that can be transmitted by single-mode optical fiber is to use large mode field optical fiber technology, that is, under the condition that the input laser power density does not exceed the laser damage threshold of the optical fiber material, a higher laser power output is achieved by increasing the optical fiber core mode field diameter (or area). For example, when the optical fiber core mode field diameter increases from the commonly used ~10μm to 100μm, the mode field area increases 100 times, and the laser power that can be transmitted by the optical fiber may increase by more than one order of magnitude. The key to large mode field optical fiber technology is to increase the fundamental mode LP 01 While increasing the mode field area, the numerical aperture (NA) of the fiber must be reduced accordingly. Otherwise, the large core diameter will support a large number of high-order modes, thereby reducing the quality of the fiber output beam. Since chalcogenide glass is usually prepared by vacuum melting-quenching, the limit of the refractive index difference between the core and cladding can be precisely controlled within 10 by adjusting the chemical composition of the core and cladding. -2 ~10 -3 Therefore, it is difficult to ensure that the common step-index fiber technology can achieve single-mode output for chalcogenide glass fiber with a core diameter of more than 40μm. To achieve large-mode field single-mode fiber with a core diameter of more than 40μm, the refractive index difference between the core and the cladding must be precisely controlled within 10 -3 (or below), must be achieved through photonic crystal fiber (PCF) technology.

[0004] The large mode field chalcogenide glass PCFs reported so far mainly include air-filled solid PCFs and all-solid (replacing air holes with low refractive index materials) PCFs. Compared with air-filled solid PCFs, all-solid PCFs can avoid the collapse and deformation of air holes during the preparation process, and there is no problem of air holes being polluted by the environment. In order to obtain a larger mode field diameter while maintaining good flexibility of the optical fiber, the number of cladding microstructure turns of the PCF needs to be reduced. Numerical simulations show that when the cladding microstructure of the all-solid large mode field PCF is 2 turns, the ratio of the diameter d of the filling column to the center distance Λ of two adjacent filling columns must be d / Λ≤0.45 to maintain single-mode transmission. In order to maintain its flexibility, the maximum core diameter of the optical fiber is about 120μm.

[0005] All-solid-state large-mode-field chalcogenide glass PCF is generally prepared by stacking and pulling. The ratio of the inner and outer diameters of the chalcogenide glass tube used in the preparation process is equal to the value of d / Λ. Therefore, it is necessary to prepare a chalcogenide glass tube with an inner and outer diameter ratio of ≤0.45. Studies have shown that the ultra-low numerical aperture NA of large-mode-field PCF makes its waveguide characteristics very sensitive to the tiny (10 -5 The non-uniform defects in the chalcogenide glass tube (such as stripes, bubbles, surface defects, etc.) can form 10 -4 ~10 -6 The refractive index fluctuation of the order of magnitude will inevitably significantly increase the transmission loss of the optical fiber. Therefore, the preparation of low-loss large-mode-field chalcogenide glass PCF requires the use of low-defect chalcogenide glass sleeves.

[0006] At present, the preparation of chalcogenide glass sheaths mainly adopts the following three methods: 1) mechanical drilling method, that is, drilling a hole along the axis of the glass rod and polishing its inner wall to obtain a sheath. This method can prepare a sheath with an inner-outer diameter ratio of ≤0.5, but the inner wall of the obtained sheath has many defects; 2) extrusion method, that is, extruding the initial glass through a mold near its softening temperature to form a sheath. This method can prepare a sheath with an inner-outer diameter ratio between 0.2 and 0.7, but the sheath obtained by this method usually has many stripes, and impurities are easily introduced during the extrusion process; 3) spinning method, that is, clamping a quartz tube filled with glass melt on a spinning machine and rotating it at high speed to form a sheath. This method can prepare a sheath with an inner-outer diameter ratio between 0.6 and 0.9. The sheath obtained by this method has few stripes, good optical uniformity, and a smooth tube wall. However, this method is difficult to prepare a chalcogenide glass sheath with an inner-outer diameter ratio of <0.6.

[0007] In 2019, Jiangsu Normal University used the stacking method to prepare an ultra-large mode field all-solid-state chalcogenide glass PCF (Optics Letters, 44 (2019) 5553-5556), with a mode field diameter of 80 μm at a wavelength of 4 μm. This PCF shows great potential in mid-infrared laser transmission and nonlinear optical applications. However, in the preparation process of this PCF, the extrusion method is used to prepare a chalcogenide glass sheath with an inner and outer diameter ratio of ≤ 0.45. There are many non-uniform defects in the prepared sheath, which will inevitably enter the cladding microstructure of the PCF, ultimately resulting in the prepared PCF showing a high transmission loss (5.2 dB / m@4 μm), making it difficult for the PCF to transmit higher laser power. Summary of the invention

[0008] In view of the problem of high transmission loss of the all-solid-state large mode field chalcogenide glass PCF prepared by the prior art, the present invention provides an improved preparation method. In the process of preparing PCF, a low-defect chalcogenide glass composite sheath with an inner-outer diameter ratio of ≤0.45 is obtained by means of a spiral tube technology. While achieving the microstructure size of the PCF, the defects on the core / cladding interface are significantly reduced, thereby significantly reducing the transmission loss of the PCF.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing an all-solid-state large mode field chalcogenide glass PCF comprises the following steps:

[0011] ① Preparation of substrate chalcogenide glass composite sleeve:

[0012] The method comprises the following steps: synthesizing a base chalcogenide glass (with a refractive index of n1) in a large vacuum quartz tube and a small vacuum quartz tube by a melting-quenching technique; preparing the base chalcogenide glass in the large vacuum quartz tube into a base chalcogenide glass sleeve A1 with inner and outer diameters of D2 and D1, respectively, and preparing the base chalcogenide glass in the small vacuum quartz tube into a base chalcogenide glass sleeve A2 with inner and outer diameters of d2 and d1, respectively; cutting open both ends of the large vacuum quartz tube and the small vacuum quartz tube, pouring out the base chalcogenide glass sleeve A1 and the base chalcogenide glass sleeve A2, and inserting the base chalcogenide glass sleeve A2 into the base chalcogenide glass sleeve A1 to form a base chalcogenide glass composite sleeve; the inner diameter D2 of the base chalcogenide glass sleeve A1 is greater than the outer diameter d1 of the base chalcogenide glass sleeve A2, and the ratio of the inner diameter d2 of the base chalcogenide glass sleeve A2 to the outer diameter D1 of the base chalcogenide glass sleeve A1 is 0.4-0.45.

[0013] ②Preparation of filled chalcogenide glass rod:

[0014] A filling chalcogenide glass (refractive index n2) is synthesized in a vacuum quartz tube by a melting-quenching technique; the two ends of the vacuum quartz tube are cut to obtain a filling chalcogenide glass rod with a diameter d3. The refractive index n2 of the filling chalcogenide glass is less than the refractive index n1 of the base chalcogenide glass; and the diameter d3 of the filling chalcogenide glass rod is less than the inner diameter d2 of the base chalcogenide glass sleeve A2.

[0015] ③Preparation of substrate chalcogenide glass restraining sleeve:

[0016] The base chalcogenide glass is synthesized in a vacuum quartz tube by using a melting-quenching technique; the synthesized base chalcogenide glass is extruded into a base chalcogenide glass restraining sleeve by using an atmosphere protection extrusion technique. The base chalcogenide glass restraining sleeve has a circular shape, an inner hole is a regular hexagon, and the diagonal length of the regular hexagon is d4.

[0017] ④ Preparation of chalcogenide glass composite thin rods:

[0018] The prepared filled chalcogenide glass rod is inserted into a base chalcogenide glass composite sleeve to form a chalcogenide glass composite rod; the chalcogenide glass composite rod is drawn into a chalcogenide glass composite thin rod, wherein the diameter d5 of the chalcogenide glass composite thin rod is less than 1 / 5 of the diagonal length d4 of the inner hole of the base chalcogenide glass restraining sleeve.

[0019] ⑤Preparation of substrate chalcogenide glass thin rods:

[0020] The base chalcogenide glass is synthesized in a vacuum quartz tube by using a melting-quenching technique; the base chalcogenide glass is drawn into a base chalcogenide glass thin rod, wherein the diameter d6 of the base chalcogenide glass thin rod is equal to the diameter d5 of the chalcogenide glass composite thin rod.

[0021] ⑥Assembly of PCF preform:

[0022] The chalcogenide glass composite thin rods are arranged in a densely stacked manner in a substrate chalcogenide glass restraining sleeve so as to fill the internal space of the substrate chalcogenide glass restraining sleeve; the substrate chalcogenide glass composite thin rod is used to replace a chalcogenide glass composite thin rod at the geometric center of the substrate chalcogenide glass restraining sleeve, thereby obtaining a PCF preform rod.

[0023] ⑦Pulled PCF

[0024] The PCF preform is drawn into a fully solid large mode field chalcogenide glass PCF.

[0025] Preferably, a difference D2-d1 between an inner diameter D2 of the substrate chalcogenide glass sleeve A1 and an outer diameter d1 of the substrate chalcogenide glass sleeve A2 is ≤0.2 mm.

[0026] Preferably, the difference d2-d3 between the diameter d3 of the thin chalcogenide glass filling rod and the inner diameter d2 of the base chalcogenide glass sleeve A2 is ≤0.2 mm.

[0027] Preferably, the relationship between the diameter d5 of the chalcogenide glass composite thin rod and the diagonal length d4 of the inner hole of the base chalcogenide glass restraining sleeve is d4-5d5≤0.4 mm.

[0028] Preferably, the core diameter of the all-solid-state large mode field chalcogenide glass PCF is 60-120 μm.

[0029] Preferably, the difference n1-n2 between the refractive index n1 of the base chalcogenide glass and the refractive index n2 of the filling chalcogenide glass is greater than 0.2.

[0030] Preferably, the softening temperature difference between the base chalcogenide glass and the filling chalcogenide glass is ≤10°C.

[0031] Preferably, drawing the chalcogenide glass composite thin rod, extruding the base chalcogenide glass restraining sleeve, drawing the base chalcogenide glass thin rod, and drawing the PCF are all performed under the protection of nitrogen or argon.

[0032] Beneficial effects:

[0033] 1. The present invention uses the spiral tube technology to prepare size-matched low-defect chalcogenide glass thick and thin sleeves, and inserts the thin sleeve into the thick sleeve to form a composite sleeve. The inner and outer diameter ratio of the composite sleeve can be easily achieved to be ≤0.45. Using this composite sleeve to prepare an all-solid-state large-mode field chalcogenide glass PCF can significantly reduce the defects on the core / cladding interface and reduce the transmission loss of the optical fiber.

[0034] 2. The method of the present invention can prepare a flexible all-solid-state large-mode-field chalcogenide glass PCF with a maximum core diameter of 120 μm, and the minimum transmission loss of the optical fiber can be reduced to below 1 dB / m, thereby meeting some practical application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the cross-sectional structure of the all-solid-state large mode field chalcogenide glass photonic crystal optical fiber of the present invention.

[0036] Figure 2 It is a schematic diagram of the cross-sectional structure of the all-solid-state large mode field chalcogenide glass photonic crystal optical fiber preform of the present invention.

[0037] Figure 3 This is a scanning electron microscope photograph of the cross section of the all-solid-state large mode field chalcogenide glass photonic crystal fiber prepared in Example 1.

[0038] In the figure, 1 is a substrate chalcogenide glass; 2 is a filling chalcogenide glass; 3 is a substrate chalcogenide glass restraining sleeve; 4 is a chalcogenide glass composite thin rod; 5 is a substrate chalcogenide glass thin rod. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention should not be limited thereto.

[0040] like Figure 1 As shown, the all-solid-state large mode field chalcogenide glass PCF prepared by the present invention comprises a base chalcogenide glass 1 and a filling chalcogenide glass 2, the refractive index n1 of the base chalcogenide glass 1 and the refractive index n2 of the filling chalcogenide glass satisfying n1-n2>0.2, and the softening temperature difference between the base chalcogenide glass 1 and the filling chalcogenide glass 2 is ≤10°C; the filling chalcogenide glass 2 is columnarly embedded in the base chalcogenide glass 1, and is arranged in a double-layer periodic manner along the center line of the base chalcogenide glass 1; the area surrounded by the inner layer of the filling chalcogenide glass is the core of the optical fiber, and the double-layer periodically arranged structure composed of the filling chalcogenide glass and the base chalcogenide glass forms the cladding of the optical fiber; the ratio d / Λ of the diameter d of the filling chalcogenide glass column to the spacing Λ between two adjacent filling chalcogenide glass columns is 0.40 to 0.45. The preparation method of the optical fiber comprises the following steps:

[0041] ① Preparation of substrate chalcogenide glass composite sleeve:

[0042] The base chalcogenide glass 1 is synthesized in a large vacuum quartz tube and a small vacuum quartz tube by a melting-quenching technique; the base chalcogenide glass 1 in the large vacuum quartz tube is prepared into a base chalcogenide glass sleeve A1 with inner and outer diameters D2 and D1, respectively, and the base chalcogenide glass 1 in the small vacuum quartz tube is prepared into a base chalcogenide glass sleeve A2 with inner and outer diameters d2 and d1, respectively; the two ends of the large vacuum quartz tube and the small vacuum quartz tube are cut open, and the inner and outer diameters are poured out. A substrate chalcogenide glass sleeve A1 and a substrate chalcogenide glass sleeve A2 are provided, and the substrate chalcogenide glass sleeve A2 is inserted into the substrate chalcogenide glass sleeve A1 to form a substrate chalcogenide glass composite sleeve; the difference D2-d1 between the inner diameter D2 of the substrate chalcogenide glass sleeve A1 and the outer diameter d1 of the substrate chalcogenide glass sleeve A2 is ≤0.2 mm, and the ratio of the inner diameter d2 of the substrate chalcogenide glass sleeve A2 to the outer diameter D1 of the substrate chalcogenide glass sleeve A1 is 0.4 to 0.45.

[0043] ②Preparation of filled chalcogenide glass rod:

[0044] A filling chalcogenide glass 2 is synthesized in a vacuum quartz tube by using a melting-quenching technique; both ends of the vacuum quartz tube are cut to obtain a filling chalcogenide glass rod with a diameter of d3; the diameter d3 of the filling chalcogenide glass rod is smaller than the inner diameter d2 of the base chalcogenide glass sheath A2; the difference d2-d3 between the diameter d3 of the filling chalcogenide glass thin rod and the inner diameter d2 of the base chalcogenide glass sheath A2 is ≤0.2 mm.

[0045] ③Preparation of base chalcogenide glass restraining sleeve 3:

[0046] The base chalcogenide glass 1 is synthesized in a vacuum quartz tube by a melting-quenching technique; the synthesized base chalcogenide glass is extruded into a base chalcogenide glass restraining sleeve 3 under nitrogen or argon protection by an atmosphere protection extrusion technique (see Figure 2 ), the outer shape of the base chalcogenide glass restraining sleeve is circular, the inner hole is a regular hexagon, and the diagonal length of the regular hexagon is d4.

[0047] ④ Preparation of chalcogenide glass composite thin rod 4:

[0048] The prepared filled chalcogenide glass rod is inserted into the base chalcogenide glass composite sleeve to form a chalcogenide glass composite rod; the chalcogenide glass composite rod is drawn under nitrogen or argon protection to form a chalcogenide glass composite thin rod 4 (see Figure 2 ); the relationship between the diameter d5 of the chalcogenide glass composite thin rod 4 and the diagonal length d4 of the inner hole of the base chalcogenide glass restraining sleeve 3 is d4-5d5≤0.4mm.

[0049] ⑤Preparation of substrate chalcogenide glass thin rod 5:

[0050] The base chalcogenide glass 1 is synthesized in a vacuum quartz tube by using a melting-quenching technique; the base chalcogenide glass 1 is drawn into a base chalcogenide glass thin rod 5 under the protection of nitrogen or argon (see Figure 2 ), the diameter d6 of the substrate chalcogenide glass thin rod 5 is equal to the diameter d5 of the chalcogenide glass composite thin rod.

[0051] ⑥Assembly of photonic crystal fiber preform:

[0052] The chalcogenide glass composite thin rods 4 are arranged in a densely stacked manner in the base chalcogenide glass binding sleeve 3 so as to fill the internal space of the base chalcogenide glass binding sleeve 3; the chalcogenide glass composite thin rods 4 at the geometric center of the base chalcogenide glass binding sleeve 3 are replaced with base chalcogenide glass thin rods 5, thereby obtaining a photonic crystal fiber preform.

[0053] ⑦Drawing photonic crystal fiber

[0054] The photonic crystal fiber preform is drawn under the protection of nitrogen or argon into a fully solid large mode field chalcogenide glass photonic crystal fiber with a core diameter of 60 to 120 μm.

[0055] Example 1

[0056] In this embodiment, the chemical composition of the base chalcogenide glass of the all-solid-state large mode field chalcogenide glass photonic crystal fiber is As 40 S 60 , its refractive index at 4 μm wavelength is 2.414, and its softening temperature is 262°C; the chemical composition of the chalcogenide glass is Ge 12 As 20 S 68, its refractive index at a wavelength of 4μm is 2.210, and its softening temperature is 272℃; the ratio of the diameter d of the filled chalcogenide glass column to the spacing Λ between two adjacent filled chalcogenide glass columns is 0.425. In the preparation of the optical fiber, the inner and outer diameters of the base chalcogenide glass sleeve A1 are 13.0mm (D2) and 19.0mm (D1), respectively, and the inner and outer diameters of the base chalcogenide glass sleeve A2 are 8.1mm (d2) and 12.9mm (D1), respectively; the diameter of the filled chalcogenide glass rod is 8.0mm (d3); the outer diameter of the base chalcogenide glass binding sleeve is 12.4mm, and the diagonal length of the inner hole regular hexagon is 6.7mm (d4); the diameter of the chalcogenide glass composite thin rod is 1.3mm (d5); the diameter of the base chalcogenide glass thin rod is 1.3mm (d6); the diameter of the drawn optical fiber is about 600μm, and the corresponding core diameter is about 100μm.

[0057] A scanning electron microscope (JSM-6510) was used to observe the cross section of the optical fiber. The truncation method was used to test the transmission loss of the optical fiber. An optical parametric amplifier (Light Conversion Orphrus) was used as the infrared light source, and an infrared beam quality analyzer (Dataray WinCamD-IR-BB) was used to detect the optical fiber output mode.

[0058] The test results of this embodiment are as follows: Figure 3 This is a scanning electron microscope photograph of the cross-section of the optical fiber finally prepared in this implementation. The optical fiber diameter is 598.4μm, the core diameter is 99.8μm, the diameter d of the chalcogenide glass column filled is 26.8μm, the spacing Λ between two adjacent chalcogenide glass columns filled is 63.3μm, and d / Λ is 0.423; the optical fiber loss at a wavelength of 3μm is 0.48dB / m, and the optical fiber output spot is single-mode; the optical fiber has good flexibility, and its minimum bending radius is less than 9cm.

[0059] Example 2

[0060] In this embodiment, the chemical composition of the base chalcogenide glass of the all-solid-state large mode field chalcogenide glass photonic crystal fiber is Ge 12 As 24 Se 64 Its refractive index at 4 μm wavelength is 2.603 and its softening temperature is 270°C; the chemical composition of the chalcogenide glass is Ge 10 As 24 S 66, its refractive index at a wavelength of 4μm is 2.603, and its softening temperature is 266℃; the ratio of the diameter d of the filled chalcogenide glass column to the spacing Λ between two adjacent filled chalcogenide glass columns is 0.40. In the preparation of the optical fiber, the inner and outer diameters of the base chalcogenide glass sleeve A1 are 13.0mm (D2) and 20.0mm (D1), respectively, and the inner and outer diameters of the base chalcogenide glass sleeve A2 are 8.0mm (d2) and 12.8mm (D1), respectively; the diameter of the filled chalcogenide glass rod is 7.9mm (d3); the outer diameter of the base chalcogenide glass binding sleeve is 13.6mm, and the diagonal length of the inner hole regular hexagon is 7.3mm (d4); the diameter of the chalcogenide glass composite thin rod is 1.4mm (d5); the diameter of the base chalcogenide glass thin rod is 1.4mm (d6); the diameter of the drawn optical fiber is about 720μm, and the corresponding core diameter is about 120μm.

[0061] A scanning electron microscope (JSM-6510) was used to observe the cross section of the optical fiber. The truncation method was used to test the transmission loss of the optical fiber. An optical parametric amplifier (Light Conversion Orphrus) was used as the infrared light source, and an infrared beam quality analyzer (Dataray WinCamD-IR-BB) was used to detect the optical fiber output mode.

[0062] The test results of this embodiment are as follows: the optical fiber diameter is 721.5 μm, the core diameter is 120.3 μm, the diameter d of the chalcogenide glass column is 30.2 μm, the spacing Λ between two adjacent chalcogenide glass columns is 75.1 μm, and d / Λ is 0.402; the optical fiber loss at a wavelength of 3 μm is 0.67 dB / m, and the optical fiber output spot is single-mode; the optical fiber has good flexibility, and its minimum bending radius is less than 12 cm.

[0063] Example 3

[0064] In this embodiment, the chemical composition of the base chalcogenide glass of the all-solid-state large mode field chalcogenide glass photonic crystal fiber is Ge 10 As 18 Sb 10 S 62 , its refractive index at 4 μm wavelength is 2.386, and its softening temperature is 317 ° C; the chemical composition of the filled chalcogenide glass is Ge 18 As 10 S 72, its refractive index at a wavelength of 4μm is 2.126, and its softening temperature is 325℃; the ratio of the diameter d of the filled chalcogenide glass column to the spacing Λ between two adjacent filled chalcogenide glass columns is 0.45. In the preparation of the optical fiber, the inner and outer diameters of the base chalcogenide glass sleeve A1 are 13.0mm (D2) and 19.0mm (D1), respectively, and the inner and outer diameters of the base chalcogenide glass sleeve A2 are 8.6mm (d2) and 12.9mm (D1), respectively; the diameter of the filled chalcogenide glass rod is 8.4mm (d3); the outer diameter of the base chalcogenide glass binding sleeve is 12.0mm, and the diagonal length of the inner hole regular hexagon is 7.4mm (d4); the diameter of the chalcogenide glass composite thin rod is 1.4mm (d5); the diameter of the base chalcogenide glass thin rod is 1.4mm (d6); the diameter of the drawn optical fiber is about 330μm, and the corresponding core diameter is about 60μm.

[0065] A scanning electron microscope (JSM-6510) was used to observe the cross section of the optical fiber. The truncation method was used to test the transmission loss of the optical fiber. An optical parametric amplifier (Light Conversion Orphrus) was used as the infrared light source, and an infrared beam quality analyzer (Dataray WinCamD-IR-BB) was used to detect the optical fiber output mode.

[0066] The test results of this embodiment are as follows: the optical fiber diameter is 330.7 μm, the core diameter is 60.1 μm, the diameter d of the chalcogenide glass column is 17.4 μm, the spacing Λ between two adjacent chalcogenide glass columns is 38.7 μm, and d / Λ is 0.45; the optical fiber loss at a wavelength of 3 μm is 0.96 dB / m, the optical fiber output light spot is single-mode, the optical fiber has good flexibility, and its minimum bending radius is less than 5 cm.

Claims

1. A method for preparing an all-solid-state large-mode-field chalcogenide glass photonic crystal fiber, characterized in that: The following steps are included: ① Preparation of substrate chalcogenide glass composite sleeve: The base chalcogenide glass with a refractive index of n1 was synthesized in a large vacuum quartz tube and a small vacuum quartz tube respectively by using the melt-quenching technique; By adopting the spiral tube technology, the base chalcogenide glass in the large vacuum quartz tube is prepared into a base chalcogenide glass sleeve A1 with inner and outer diameters of D2 and D1 respectively, and the base chalcogenide glass in the small vacuum quartz tube is prepared into a base chalcogenide glass sleeve A2 with inner and outer diameters of d2 and d1 respectively, and D2>d1, d2 / D1=0.4-0.45; Cut open both ends of the large vacuum quartz tube and the small vacuum quartz tube, and pour out the base chalcogenide glass sleeve A1 and the base chalcogenide glass sleeve A2; Inserting the substrate chalcogenide glass sleeve A2 into the substrate chalcogenide glass sleeve A1 to form a substrate chalcogenide glass composite sleeve; ②Preparation of filled chalcogenide glass rod: The chalcogenide glass with a refractive index of n2 is synthesized in a vacuum quartz tube by melt-quenching technology, and n2<n1; Cut the two ends of the vacuum quartz tube to obtain a filled chalcogenide glass rod with a diameter of d3, and d3<d2; ③Preparation of substrate chalcogenide glass restraining sleeve: The base chalcogenide glass was synthesized in a vacuum quartz tube using a melt-quench technique; The synthesized base chalcogenide glass is extruded by atmosphere protection extrusion technology to form a cylindrical base chalcogenide glass binding tube with a regular hexagonal inner hole, wherein the diagonal length of the regular hexagonal inner hole is d4; ④ Preparation of chalcogenide glass composite thin rods: Inserting the filled chalcogenide glass rod prepared in step ② into the base chalcogenide glass composite sleeve prepared in step ① to form a chalcogenide glass composite rod; The chalcogenide glass composite rod is drawn into a chalcogenide glass composite thin rod with a diameter of d5, and d5 is less than 1 / 5d4; ⑤Preparation of substrate chalcogenide glass thin rods: The base chalcogenide glass was synthesized in a vacuum quartz tube using a melt-quench technique; The substrate chalcogenide glass is drawn into a substrate chalcogenide glass thin rod with a diameter of d6, and d6=d5; ⑥Assembly of photonic crystal fiber preform: Arranging the chalcogenide glass composite thin rods in a tightly packed manner in the base chalcogenide glass restraining sleeve so that the thin rods fill the inner space of the base chalcogenide glass restraining sleeve; A photonic crystal fiber preform is obtained by replacing a chalcogenide glass composite thin rod at the geometric center of a substrate chalcogenide glass binding sleeve with a substrate chalcogenide glass thin rod; ⑦Drawing photonic crystal fiber The photonic crystal fiber preform obtained in step ⑥ is drawn to form an all-solid-state large-mode-field chalcogenide glass photonic crystal fiber.

2. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: The difference D2-d1 between the inner diameter D2 of the substrate chalcogenide glass sleeve A1 and the outer diameter d1 of the substrate chalcogenide glass sleeve A2 is ≤0.2 mm.

3. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: The difference d2-d3 between the diameter d3 of the thin chalcogenide glass rod and the inner diameter d2 of the base chalcogenide glass sleeve A2 is ≤0.2 mm.

4. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: The relationship between the diameter d5 of the chalcogenide glass composite thin rod and the diagonal length d4 of the inner hole of the base chalcogenide glass restraining sleeve is d4-5d5≤0.4mm.

5. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: The core diameter of the all-solid-state large-mode-field chalcogenide glass photonic crystal optical fiber is 60-120 μm.

6. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: The difference n1-n2 between the refractive index n1 of the substrate chalcogenide glass and the refractive index n2 of the filling chalcogenide glass is greater than 0.

2.

7. The method for preparing an all-solid-state large mode field chalcogenide glass photonic crystal fiber according to claim 1, characterized in that: Drawing of chalcogenide glass composite thin rods, extrusion of base chalcogenide glass binding sleeves, drawing of base chalcogenide glass thin rods, and drawing of photonic crystal optical fibers are all carried out under the protection of nitrogen or argon.

Citation Information

Patent Citations

  • Method for fixing the position of a glass tube or glass rod spiral in a glass tube, glass tube assembly and the application of the same

    CN101613176A

  • Single-mode chalcogenide glass optical fiber and preparation method thereof

    CN102976607A